Performance evaluation of ECN-enabled DCCP - Mendoza, Rene C.
This research aims to investigate the effects of enabling Explicit Congestion Notification (ECN) on the Datagram Congestion control protocol (DCCP). DCCP is a transport protocol that combines congestion control and timely delivery of datagram packets. Its congestion control mechanisms are based on TCP. Hence, it also exhibits the same behavior and response to congestion as TCP. Congestion is usually detected by TCP when a packet is dropped or when it receives an ECN-marked packet. This is also the case with DCCP's Congestion Control Profiles (CCID 2 and CCID 3). We specifically focused on DCCP and ECN. Through various simulation scenarios, we evaluated DCCP's performance when both endpoints are ECN capable and compared it to DCCP using random Early Detection (default drop) and DCCP using tail drop. Performance was based on goodput, delay, packet loss rates, jitter and fairness. Results have shown that ECN-enabled DCCP's performance showed similar performance behavior seen with ECN-enabled TCP, i.e., lower average queue lengths, lower packet drop rates, and better fairness compared with tail drop.